Kolb's learning style analysis in solving HOTS questions for prospective physics teacher students - Nengah Nitriani; Darsikin Darsikin; Sahrul Saehana (Momentum: Physics Education Journal, 2022)
This study aims to analyze Kolb's Learning Style (KLS) in solving HOTS questions for prospective physics teacher students. This research is a descriptive study using a qualitative approach. The subjects of this research are second semester students who have joined the Basic Physics course for Archimedes' Principle, amounting to 46 people. The instrument used was a Kolb's Learning Style (KLS) questionnaire, which consisted of 40 statement items, 8 essay questions about HOTS, and interview guidelines. Based on the results of the study, it showed that from the maximum percentage (100%) in each Kolb's Learning Style (KLS) obtained the combination of diverger and assimilator learning styles as the highest average percentage (65.63%) in solving HOTS questions correctly compared to the other learning styles. It is followed by the accomodator (56.25%), the combination of assimilator and converger (54.17%), diverger (53.41%), assimilator (49.22%), and converger (48.61%). There are differences in Kolb's Learning Style (KLS) in solving HOTS questions for prospective physics teacher students where students still experience errors in answering questions. The forms of incorrect answers given by students include: 1) Objects with a smaller surface area must be sink, 2) Heavy objects must be sink, 3) The amount of water affects the state of floating and sinking, 4) Hollow objects always float, and 5) Objects made of something hard must be sink. Based on the results of this study, it can be concluded that the ability of prospective physics teacher students in solving HOTS questions must be trained by adjusting their learning styles.